Insights on the Application of MATLAB and Chaotic Principles to Determine the Targeted Delivery of a Smart Drug Delivery System against Cancer in the Experimental Phase: A Prospective Approach - Moni, Dr. Sivakumar Sivagurunathan (Asian Journal of Pharmaceutics (AJP), 2020)
The smart drug delivery system (SDDS) is a milestone in cancer therapy and uses nanoparticle drug delivery principles such as surface linking with monoclonal antibodies (MABs). This interaction of SDDS with cancer cells can be ascertained by the MATLAB tool and chaotic dynamic system behavioral evaluation. The successful targeting depends on the interaction between the MAB ligand and the antigenic determinants of tumor antigens. However, the target-specific SDDS is highly influenced by various factors such as spatial orientation around the tumor antigens and specific ligands of the MABs. In this study, we focused on the implications of the MATLAB tool and chaotic principles to determine target-specific treatment with SDDS.